The reaction of asset prices to macroeconomic announcements in new EU markets: Evidence from intraday data - Hanousek, Jan; Kočenda, Evžen; Kutan, Ali M. (Journal of Financial Stability, 2009)
We estimate the impact of macroeconomic news on composite stock returns in three emerging European Union financial markets (the Budapest BUX, Prague PX-50, and Warsaw WIG-20), using intraday data and macroeconomic announcements. Our contribution is twofold. We employ a larger set of macroeconomic data releases than used in previous studies and also use intraday data, an excess impact approach, and foreign news to provide more reliable inferences. Composite stock returns are computed based on 5-min intervals (ticks) and macroeconomic news are measured based on the deviations of the actual announcement values from their expectations. Overall, we find that all three new EU stock markets are subject to significant spillovers directly via the composite index returns from the EU, the U.S. and neighboring markets; Budapest exhibits the strongest spillover effect, followed by Warsaw and Prague. The Czech and Hungarian markets are also subject to spillovers indirectly through the transmission of macroeconomic news. The impact of EU-wide announcements is evidenced more in the case of Hungary, while the Czech market is more impacted by U.S. news. The Polish market is marginally affected by EU news. In addition, after decomposing pooled announcements, we show that the impact of multiple announcements is stronger than that of single news. Our results suggest that the impact of foreign macroeconomic announcements goes beyond the impact of the foreign stock markets on Central and Eastern European indices. We also discuss the implications of the findings for financial stability in the three emerging European markets.